2015
DOI: 10.1123/ijsnem.2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between General Nutrition Knowledge and Dietary Quality in Elite Athletes

Abstract: mean (Standard Deviation). A total of 101 athletes (Males: 37; Females: 64), 18.6 (4.6) years were recruited mainly from team sports (72.0%). Females scored higher than males for both nutrition knowledge (Females: 59.9%; Males: 55.6%; p = .017) and total A-ARFS (Females: 54.2% Males: 49.4%; p = .016). There was no significant influence of age, level of education, athletic caliber or team/individual sport participation on nutrition knowledge or total A-ARFS. However, athletes engaged in previous dietetic consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
6
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 0 publications
6
103
6
3
Order By: Relevance
“…Our results (45.6%) are lower than those reported by others [9,10,11,12,13,14], but are most similar to Walsh et al [15] and Spronk et al [11]. Walsh et al examined sport nutrition knowledge in Irish senior male high school rugby players (59.6% overall score), while Spronk et al [11] reported general nutrition knowledge scores of 55% in elite male athletes (≥16 years). Although our questionnaire was adapted from Walsh et al, our scores were still 15% lower.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Our results (45.6%) are lower than those reported by others [9,10,11,12,13,14], but are most similar to Walsh et al [15] and Spronk et al [11]. Walsh et al examined sport nutrition knowledge in Irish senior male high school rugby players (59.6% overall score), while Spronk et al [11] reported general nutrition knowledge scores of 55% in elite male athletes (≥16 years). Although our questionnaire was adapted from Walsh et al, our scores were still 15% lower.…”
Section: Discussioncontrasting
confidence: 92%
“…Overall, mean general nutrition or sport nutrition knowledge scores for high school athletes range from 55%–74% [9,10,11,12,13,14,15], with higher scores in females (65%–68%) [12,13,14]. Our results (45.6%) are lower than those reported by others [9,10,11,12,13,14], but are most similar to Walsh et al [15] and Spronk et al [11]. Walsh et al examined sport nutrition knowledge in Irish senior male high school rugby players (59.6% overall score), while Spronk et al [11] reported general nutrition knowledge scores of 55% in elite male athletes (≥16 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vegetable intake was higher in the female athletes: 150 in female compared with 114[61-183] g/d in male athletes. A possible explanation could be higher nutrition knowledge and dietary quality, which previously has been reported in female compared with male elite athletes (Spronk et al, 2015). The higher vegetable and associated nitrate intake in females could possibly explain the higher plasma nitrate values previously found in females compared with men, both by our research group (Jonvik et al, 2016) as well as by others (Kapil et al, 2010;Velmurugan et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Contudo, é preciso destacar que, apesar de termos o nutricionista como o profissional mais citado na indicação para o uso do suplemento, com 34,1%, o percentual de indicação por profissionais de outras áreas e o consumo sem orientação também foi elevado, não sendo esta a prática ideal, uma vez que o consumo de suplementos deve vir associado a uma alimentação equilibrada, e o nutricionista é o profissional capacitado para prescrição da dieta e promoção da alimentação saudável. Apesar do presente estudo não apresentar diferença do conhecimento sobre nutrição entre os sexos, estudos com atletas profissionais demonstraram um melhor perfil e conhecimento alimentar por mulheres 29,30 . Segundo Jacobson et al 30 , isto se deu pelo fato de que para a maioria das mulheres a orientação nutricional partiu prioritariamente de um nutricionista.…”
Section: Discussionunclassified